Global aircraft manufacturing, 2002-2011 - Brown, Jennifer; Garthwaite, Craig; Crowe, Susan; Snyder, Charlotte; Merkley, Greg (London : SAGE Publications Ltd, 2017)
At the dawn of the twenty-first century, Boeing and Airbus, the leading manufacturers of large aircraft, were locked in a battle for market share that drove down prices for their new planes. At about the same time, the two industry heavyweights began developing new aircraft families to address the future market needs they each projected. Aircraft take many years to develop, so by the time the new planes made their inaugural flights, significant changes had occurred in the global environment. First, emerging economies in the Asia-Pacific region and elsewhere were growing rapidly, spawning immediate and long-term demand for more aircraft. At the same time, changes to the market for air travel had created opportunities for new products. These opportunities had not gone unnoticed by potential new entrants, which were positioning themselves to compete against the market leaders.In October 2007, the Airbus superjumbo A380 made its first flight. The A380 carried more passengers than any other plane in history and had been touted as a solution to increased congestion at global mega-hub airports. Four years later the Boeing 787, a smaller long-range aircraft, was launched to service secondary cities in a point-to-point network.The case provides students with an opportunity to analyze the profit potential of the global aircraft manufacturing industry in 2002 and in 2011. Students can also identify the actions of participants that weakened or intensified the pressure on profits within the industry.
Originally published in Brown, J., Garthwaite, C., Crowe, S., Snyder, C., & Merkeley, G. (2016). Global aircraft manufacturing, 20022011. 5-414-754. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Boeing Aerospace Company; Airbus Industrie; Aircraft industry; Competition, Imperfect